LB1. Remdesivir for the Treatment of High-Risk Non-Hospitalized Individuals With COVID-19: A Randomized, Double-Blind, Placebo-Controlled Trial. (4th December 2021) - Hill, Joshua A; Paredes, Roger; Vaca, Carlos; Mera, Jorge; Webb, Brandon J; Perez, Gilberto; Oguchi, Godson; Ryan, Pablo; Gerstoft, Jan; Brown, Michael; Schiffer, Joshua; Brown, Samuel; et al.
Abstract: Background: Remdesivir (RDV) is a potent nucleotide prodrug inhibitor of the SARS-CoV-2 RNA-dependent RNA polymerase that has demonstrated efficacy in the treatment of patients hospitalized with moderate to severe COVID-19. This Phase 3 (GS-US-540–9012) double-blind, placebo-controlled study compared the efficacy and safety of 3 days of RDV to standard of care in non-hospitalized, high-risk participants with confirmed COVID-19. Table 1. COVID-19 related hospitalization or death, COVID-19 related medically attended visits or death, and Treatment Emergent Adverse Events Methods: Participants were randomly assigned 1:1 to receive intravenous (IV) RDV (200 mg on day 1, 100 mg on days 2 to 3) or placebo. The primary efficacy endpoint was composite COVID-19 hospitalization or all-cause death by day 28 and compared using Cox proportional hazards model with baseline stratification factors as covariates. The primary safety endpoint was proportion of participants with treatment-emergent adverse events. Study enrollment was terminated early for administrative reasons in light of the evolving pandemic. Results: 562 patients underwent randomization and started their assigned treatment (279, RDV; 283, placebo). Baseline demographics and characteristics were balanced across arms. Overall, 52% were male, 44% were Hispanic/Latino ethnicity and 30% were ≥ 60 years old. The most common comorbidities were diabetes mellitus (62%), obesity (56%; median BMI, 30.7), and hypertension (48%). Median baseline SARS-CoV-2 RNA nasopharyngeal viral load was 6.2 log10 copies/mL. Treatment with RDV significantly reduced COVID-19 hospitalization or all-cause death by day 28 (HR, 0.13; 95% CI, 0.03 – 0.59; p = 0.008; Table 1) compared to placebo. Participants receiving RDV also had significantly lower risk for COVID-19-related medically attended visits or all-cause death by day 28 compared to placebo (HR, 0.19; 95% CI, 0.07 – 0.56; p = 0.002; Table 1). No deaths occurred in either arm by day 28. There was no difference between arms in time-weighted average change in nasopharyngeal viral loads from baseline up to day 7. The proportion of patients with AEs was similar between arms (Table 1); the most common AEs in the RDV arm were nausea (11%), headache (6%), and diarrhea (4%). Conclusion: A 3-day course of IV RDV was safe, well tolerated and highly effective at preventing COVID-19 related hospitalization or death in high-risk non-hospitalized COVID-19 patients. Disclosures: Joshua A. Hill, MD, Allogene (Individual(s) Involved: Self): Consultant; Allovir (Individual(s) Involved: Self): Consultant, Grant/Research Support; Amplyx (Individual(s) Involved: Self): Consultant; Covance/CSL (Individual(s) Involved: Self): Consultant; CRISPR (Individual(s) Involved: Self): Consultant; Gilead (Individual(s) Involved: Self): Consultant, Grant/Research Support; Karius: Grant/Research Support, Scientific Research Study Investigator; Medscape (Individual(s) Involved: Self): Consultant; Octapharma (Individual(s) Involved: Self): Consultant; OptumHealth (Individual(s) Involved: Self): Consultant; Takeda (Individual(s) Involved: Self): Consultant, Grant/Research Support, Scientific Research Study Investigator Roger Paredes, MD, PhD, Gilead Sciences, Inc (Grant/Research Support, Scientific Research Study Investigator, Advisor or Review Panel member) Carlos Vaca, MD, Gilead Sciences, Inc (Scientific Research Study Investigator) Jorge Mera, MD, Gilead Sciences, Inc (Consultant, Study Investigator (payment to employer not self)) Gilberto Perez, MD, Gilead Sciences, Inc (Scientific Research Study Investigator) Godson Oguchi, MD, Gilead Sciences, Inc (Scientific Research Study Investigator) Pablo Ryan, MD PhD, Gilead Sciences, Inc (Grant/Research Support, Scientific Research Study Investigator, Advisor or Review Panel member) Jan Gerstoft, MD, Gilead Sciences, Inc (Other Financial or Material Support, Study Investigator (payment to employer)) Michael Brown, FRCP PhD, Gilead Sciences, Inc (Scientific Research Study Investigator, Investigator for numerous remdesivir trials (employer received compensation)) Morgan Katz, MD, MHS, Roche (Individual(s) Involved: Self): Advisor or Review Panel member; Skinclique (Individual(s) Involved: Self): Consultant Gregory Camus, PhD, Gilead Sciences (Employee, Shareholder) Danielle P. Porter, PhD, Gilead Sciences (Employee, Shareholder) Robert H. Hyland, DPhil, Gilead Sciences, Inc (Shareholder, Other Financial or Material Support, Employee during the conduct of this trial) Shuguang Chen, PhD, Gilead Sciences, Inc (Employee, Shareholder) Kavita Juneja, MD, Gilead Sciences, Inc (Employee) Anu Osinusi, MD, Gilead Sciences, Inc (Employee, Shareholder) Frank Duff, MD, Gilead Sciences, Inc (Employee, Shareholder) Robert L. Gottlieb, MD, Eli Lilly (Scientific Research Study Investigator, Advisor or Review Panel member)Gilead Sciences (Scientific Research Study Investigator, Advisor or Review Panel member, Other Financial or Material Support, Gift in kind to Baylor Scott and White Research Institute for NCT03383419)GSK (Advisor or Review Panel member)Johnson and Johnson (Scientific Research Study Investigator)Kinevant (Scientific Research Study Investigator)Roche/Genentech (Scientific Research Study Investigator)